Re-domestication of Internet Technologies: Digital Exclusion or Digital Choice?. Issue 6 (6th November 2021) - Grošelj, Darja
Abstract: Internet access is now characterized by multi-device, mobile, and ubiquitous access. We explore the changing nature of internet access by focusing on social practices that shape the position and role of internet technologies in everyday internet use. Drawing on the domestication framework, the study uses data from qualitative interviews with UK internet users to explore how technologies are re-domesticated. Three practices encompassing how internet users develop and maintain internet access were identified: spotlighting, distributing, and making do. In addition, orientation, understanding, play, and communication internet dependencies were examined to determine how individuals relate to internet technologies. The practices of re-domestication reflect differences in the role that internet technologies play in individuals' daily lives, and differences in the availability of offline resources. The study contributes to our understanding of the mechanisms underlying the development and maintenance of internet access, depending on whether access arrangements are shaped by digital exclusion or choice. Lay Summary: As internet access becomes more complex, it is important to understand how people interact with the various internet technologies they use. Theoretically, the concept of re-domestication suggests that the meanings, roles, and uses of old technologies can shift as new technologies are adopted. The concept of internet centrality, which includes orientation, understanding, play, and communication dependencies, illustrates the role of internet technologies in individuals' daily lives. The study draws on 29 qualitative interviews with UK internet users. Three distinct practices of re-domestication were identified: "spotlighting, " where one device becomes the predominant way people go online; "distributing, " which involves access where different devices are used and the choice of a particular device depends on the contextual factors of internet use; and "making do, " where users struggle to maintain internet access, resulting in access being restricted. In addition, the analysis of internet centrality showed that different re-domestication practices also reflect differences in what role internet technologies play in individuals' daily lives: Users who engaged in spotlighting or making do practices were more inclined to value the internet for relaxation and pastime (play dependency), whereas those who engaged in distributing practices were more inclined to value the internet for meaning making (understanding dependency).